Comparison of Different Exercise Modalities on Neuronal Plasticity and Spatial Memory - Tavor Ben-Zeev; Chagai Levi; Nicholas A. Ratamess; Henriette van Praag; Jay R. Hoffman (Medicine & Science in Sports & Exercise, 2026)
Purpose: The relationship between exercise and brain function has been studied extensively; however, whether different exercise modalities promote hippocampal neurogenesis and cognitive function through shared or distinct biological pathways remains unclear. This study examined the effects of endurance training (ET), resistance training (RT), and high-intensity interval training (HIIT) on hippocampal neurogenesis, spatial memory, and neurotrophic factors. Methods: Forty 3-month-old male C57BL/6J mice were randomized to control (SED), ET, RT, or HIIT groups. Following the training intervention, adult hippocampal neurogenesis was assessed in the dentate gyrus using BrdU⁺/NeuN⁺ immunolabeling. Hippocampal measures of neurotrophic factors, including brain-derived neurotrophic factor (BDNF), insulin-like growth factor-1 (IGF-1), and fibronectin type III domain–containing protein (FNDC5), were quantified. Spatial memory was evaluated using the Barnes maze. Results: All exercise modalities increased the number of BrdU⁺/NeuN⁺ cells compared with sedentary controls (RT, p